2014
DOI: 10.1073/pnas.1419576111
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological protection of retinal pigmented epithelial cells by sulindac involves PPAR-α

Abstract: The retinal pigmented epithelial (RPE) layer is one of the major ocular tissues affected by oxidative stress and is known to play an important role in the etiology of age-related macular degeneration (AMD), the major cause of blinding in the elderly. In the present study, sulindac, a nonsteroidal antiinflammatory drug (NSAID), was tested for protection against oxidative stressinduced damage in an established RPE cell line . Besides its established antiinflammatory activity, sulindac has previously been shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…We are not the firsts to point out the potential importance of NRs and particularly, PPARs in controlling several AMD-pathogenic pathways (46)(47)(48)(49)(50)(51). Indeed, it has been shown that PPAR-a agonists protect RPE cells from an oxidative stress insult in vitro (52) and reduce angiogenesis in mouse models of neovascular AMD (53). PPAR-b/d modulation seems to play different roles in dry AMD and neovascular AMD models.…”
Section: Discussionmentioning
confidence: 96%
“…We are not the firsts to point out the potential importance of NRs and particularly, PPARs in controlling several AMD-pathogenic pathways (46)(47)(48)(49)(50)(51). Indeed, it has been shown that PPAR-a agonists protect RPE cells from an oxidative stress insult in vitro (52) and reduce angiogenesis in mouse models of neovascular AMD (53). PPAR-b/d modulation seems to play different roles in dry AMD and neovascular AMD models.…”
Section: Discussionmentioning
confidence: 96%
“…The two mechanisms that have been of interest to us are a protective pharmacological preconditioning response [31, 32]and the Msr protein repair system. The present studies describe for the first time activators of recombinant MsrA and MsrB that are derivatives of the naturally occurring antibiotic fusaricidin A [28].…”
Section: Discussionmentioning
confidence: 99%
“…We are particularly interested in studying oxidative damage in the retina, where we have recently shown that sulindac, a substrate for the Msr enzymes, initiates a pharmacological preconditioning response that protects retinal pigmented epithelial (RPE) cells against oxidative damage [32]. MsrA is found in high concentrations in RPE cells [34], and the retina is very sensitive to oxidative damage which can lead to loss of the photoreceptor cells that are involved in diseases including age related macular degeneration, diabetic retinopathy, and the genetic disease, retinitis pigmentosa.…”
Section: Discussionmentioning
confidence: 99%
“…For example, peroxisome proliferator-activated receptor α (PPARA, Figure 3(c)) is the pharmacological target of fibrates such as fenofibrate, clofibrate, and bezafibrate [35]. PPARA is associated with both antioxidant and anti-inflammatory activities and has previously been suggested as a therapeutic target in AMD [9597]. In fact, several clinical trials have revealed that fenofibrate can improve diabetic retinopathy [98, 99], which shares some pathophysiological mechanisms with AMD, including OS [100, 101].…”
Section: Integrative Approaches In the Search For Therapeutic Targmentioning
confidence: 99%